NINETEENTH CENTURY NAVIES’ ROLE IN DEVELOPING AN UNDERSTANDING OF THE PACIFIC COAST OF CENTRAL AMERICA (1730-1900) - León Sáenz, Jorge (2018)
Early 19th Century knowledge of nautical affairs was scant, regarding the Pacific coast of Central America.  Prior to 1800, the main source of information on that coast was Spanish “derroteros” or sailing directions. Between 1808-1826, British commercial and maritime interests replaced those of Spain in the region. British ships cruising the coast, needed better maritime charts, and thus surveying became an important task for the Royal Navy. From the mid 1830’s, British Admiralty charts became the main source of navigational information.  Then the French Navy and later the United States Navy became involved in the survey of Pacific coast ports and harbors. During 1873-1907, Costa Rica established a small naval force due to regional political problems. When in the 1880s geopolitical interest arose in building a canal across Central America, the Costarrican Government decided it required information about its Pacific coast, carrying out surveys and publishing maritime charts and instructions for inshore navigation.  Altogether, surveying activities by different navies resulted in a major improvement in nautical knowledge compared to a century earlier.